(3GdCNVQis - (3YHO GdQMef Hf eMeO GdUZjQ GdGNVQj, CHh RjO,J (B983 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
" (3Chd eG jLH Ydi GdecdaI (B" (3GdYGbd GdHGdZ HCMO ehLHGJ GdHdhZ ef efi Ch Oe Ch Med Ch KeGfjI YTQ MhdkG s
(3BNQgG (B:s
(3hef jJbjf GdceGd Yed dfaSg hJQc GdYOdjjf Ci SDGd GdYOdjf hEf de jJQcg jWdb Edi Cf jcKQ GdfGS Ndag ajJhd Gdjbjf hjQLY Edjge s
(3GdeNWhW eeRb hHgG BKGQ QWhHI hCcd CQVI hgh eJBcd ef GdCWQGas
(3hgj eaccgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3Gdabg GdeGdcjs